2021
DOI: 10.1039/d1dt02000e
|View full text |Cite
|
Sign up to set email alerts
|

Heavy silylchalcogenido lanthanates synthesis Ph4P[Cp3La–ESiMe3] (E = S, Se, and Te) via fluoride-induced demethylation of dimethylcarbonate to Ph4P[OCO2Me] key intermediate

Abstract: We report a new high-yield synthesis of so far not accessible tetraphenylphosphonium methylcarbonate Ph4P[OCO2Me] via solvothermal fluoride-induced demethylation and MeF elimination at Me2CO3 (DMC) by Ph4P-F, XRD structurally characterized as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…When investigating N-heterocyclic thiols, we could obtain SF5−quinoline 37 and several 2-SF5 pyridine derivatives (38−41) in good to excellent yields. With increasing electrondeficiency (41,42) we detected an increasing amount of 2-fluorination instead of pentafluorosulfanylation, which we account to a nucleophilic aromatic substitution (SNAr) side reactions. To obtain compounds with multiple SF5 groups, we tested several aryl di-or tri-thiols and obtained the bis-and tris-pentafluorosulfanylated product (43)(44)(45)(46)(47)49) in good to excellent yields.…”
Section: Main Textmentioning
confidence: 73%
See 1 more Smart Citation
“…When investigating N-heterocyclic thiols, we could obtain SF5−quinoline 37 and several 2-SF5 pyridine derivatives (38−41) in good to excellent yields. With increasing electrondeficiency (41,42) we detected an increasing amount of 2-fluorination instead of pentafluorosulfanylation, which we account to a nucleophilic aromatic substitution (SNAr) side reactions. To obtain compounds with multiple SF5 groups, we tested several aryl di-or tri-thiols and obtained the bis-and tris-pentafluorosulfanylated product (43)(44)(45)(46)(47)49) in good to excellent yields.…”
Section: Main Textmentioning
confidence: 73%
“…4A-i). Furthermore, testing various tetraalkylammonium or phosphonium salts showed that besides the corresponding chlorides and bromides, also bench-stable tetraphenylfluorophosphane (PPh4F) (41) was effective (Fig. 4A-ii).…”
Section: Main Textmentioning
confidence: 99%